Association of Body Mass Index and Waist Circumference With Dental Caries and Consequences of Untreated Dental Caries Among 12- to 14-Year-old Boys: A Cross-Sectional Study - Ravi Kumar Gudipaneni; Rakan Menwer Albilasi; Omer HadiAlrewili; Mohammad Khursheed Alam; Santosh R. Patil; Faisal Saeed (Elsevier, 2021)
Objective: To evaluate the association between body mass index (BMI) and waist circumference (WC) and dental caries (DC), and the clinical consequences of untreated dental caries (U-DC) among 12- to 14-year-old male public-school adolescents in the Northern Province, Saudi Arabia. Methods: The demographic and anthropometric measurements of 302 boys 12 to 14 years of age (mean: 12.5 years) were recorded. BMI and central obesity (based on WC) were measured. The decayed-missing-filled teeth (DMFT) index was used to record DC. The pulp involvement, ulceration, fistula, abscess (PUFA) index was used to quantify the clinical consequences of U-DC. Multiple logistic regression analysis was performed to evaluate the risk factors related to DC and clinical consequences of U-DC. Results: A high prevalence of DC was found in adolescents who were underweight according to BMI and nonobese based on WC (46.7% vs 34.5%). The association between underweight (BMI) and obese (WC) with DC (odds ratio [95% CI]) was 1.91 (0.87, 4.18) and 0.34 (0.18, 0.63), respectively, while with PUFA (adjusted odds ratio [AOR]; 95%CI), it was 1.76 (0.76, 4.09) and 0.19 (0.06, 0.63) respectively. The logistic regression model showed that consuming sugar more than once a day led to a 2.87-fold greater likelihood of DC (AOR [95% CI] = 2.87 [1.68, 4.88]) and a 3.91-fold greater likelihood of mean PUFA score (AOR [95% CI] = 3.91 [2.05, 7.44]. Conclusion: High risks for DC and clinical consequences of U-DC were observed among underweight and nonobese adolescent males. The frequency of sugar consumption was significantly associated with both conditions.